Gambaran Tingkat Kecemasan Pasien Anak Usia Sekolah yang Menjalani Hospitalisasi - Supartini, Sri; Istiqomah, Nurul; Sarifah, Siti; Mintarsih, Sri (Profesi (Profesional Islam) : Media Publikasi Penelitian, 2023)
Background: anxiety is a problem that often arises in children who are undergoing hospitalization. That's because the children feel that the environment at the hospital is very different from the environment at home, that's because they're separated from their families and feel sick because of their illness, which has an impact on the child's psychological condition. Hospitalization stress is an event or problem that often occurs in hospitalized patients, especially in children. In this study, it was shown that the cause of anxiety in children was separation from those closest to them, which led to the behavior of children crying when they were first admitted to the hospital, screaming when they were crying, and not wanting to be approached by other people, looking for parents, crying. when parents leave the room, refuse and even send other people they think are strangers, and refuse treatment or care. Purpose: to describe the level of anxiety in young children undergoing inpatient treatment at Sarila Husada Hospital, Sragen. Research method: this study uses a quantitative description method. The population of this study were early childhood children who were undergoing hospitalization at Sarila Husada Hospital, Sragen with a total of 40 sample. This study uses a questionnaire instrument. This research study uses data analysis that does not change. The results of these 40 sample based on the age of 10-12 years amounted to 21 sample (52.5%), which were dominated by women, namely 22 sample (55.0%), based on the majority of the length of treatment there were 22 sample (55.0%), who treated for 4-7 days at a moderate level of anxiety, namely 22 sample (55.0%).